2014
DOI: 10.1007/s00406-014-0488-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased spectral entropy modulation in patients with schizophrenia during a P300 task

Abstract: Spectral entropy (SE), also known as Shannon entropy, is a useful parameter for quantifying the global regularity of the electroencephalographic (EEG) signal. Hence, it is of interest in the assessment of the electrophysiological correlates of cognitive processing in schizophrenia. However, to date, SE has been barely used in studies comparing resting EEG recordings between patients and controls. In this work, we compared SE between resting baseline [-250 0] ms and active task [150 550] ms windows of a P300 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 42 publications
10
64
1
3
Order By: Relevance
“…In contrast, P3b seems to be related to conscious top-down target processing, likely contributing to processing the stimulus information and performing cognitive response (Polich, 2007;Strobel et al, 2008). In previous reports, we found a blunted ERP modulation in Sz as response to both target (Bachiller et al, 2014) and distractor (Bachiller et al, 2015b) tones during an oddball paradigm. Thus, the analysis of the differences in neural pattern generators between Sz patients and healthy controls becomes an interesting research topic to clarify the neural substrate of reduced P300 amplitude in Sz.…”
contrasting
confidence: 46%
“…In contrast, P3b seems to be related to conscious top-down target processing, likely contributing to processing the stimulus information and performing cognitive response (Polich, 2007;Strobel et al, 2008). In previous reports, we found a blunted ERP modulation in Sz as response to both target (Bachiller et al, 2014) and distractor (Bachiller et al, 2015b) tones during an oddball paradigm. Thus, the analysis of the differences in neural pattern generators between Sz patients and healthy controls becomes an interesting research topic to clarify the neural substrate of reduced P300 amplitude in Sz.…”
contrasting
confidence: 46%
“…There are few studies that conducted discriminant analyses for differentiating SCH and control subjects. For instance, Bachiller et al [21] used linear discriminant analysis (LDA) applied to Shannon spectral entropy to achieve an accuracy of 0.77. In other study, Sabeti et al [22] used LDA and adaptive boosting with five spectral and nonlinear features to classify SCH group, achieving a maximum accuracy of 0.91.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we computed RP in order to study the spectral features of the EEG recordings, assess the validity of the database by comparing the results with those of a different one [15], and check its relationship with KLD. It is worth pointing out that the TFR needs to be normalized to the sum of the absolute values in all bands in order for RP to be a relative measure.…”
Section: Relative Powermentioning
confidence: 99%
“…Several methods have been used to analyze transient dynamics in neural activity during an auditory oddball task or during resting-state. Such measures, of a time-dependent nature, include wavelet entropy [6,13], multiscale entropy [14], median frequency [12,15] and relative power (RP) [15], among others. Many of these studies have found widespread lower neural reorganization (i.e., transient dynamical reorganization of brain activity during an attentional process) for SCH subjects compared to controls during the active task response [6,12,15].…”
Section: Introductionmentioning
confidence: 99%